Private household concepts and their operationalisation in cross-national social surveys - Hoffmeyer-Zlotnik, Jürgen H. P. (Metodološki zvezki, 2009)
Starting with the input-harmonised and methodically controlled European Social Survey (ESS), moving on to the national censuses, and then turning our attention to the three groups participating in surveys (researchers, interviewers and respondents), we discover that the private household concept is defined in many different ways. Each of these definitions entails a different household composition. Using an example, we demonstrate how different definitions of private household (and different household compositions) affect the socio-economic status and income of the household. Ultimately, a variation in the definition of private household is enough to raise or lower the national poverty line. Our findings lead us to propose that "private household" be operationalised across countries in a way that guarantees that persons can be unequivocally assigned to households on the basis of inclusion and exclusion criteria.
Keywords: Družboslovne ankete; Social surveys; Gospodinjstva; Households; družboslovno raziskovanje; mednarodne primerjave; European Union; Evropska unija